Biomarker profiles associated with reverse ventricular remodelling in patients with heart failure and a reduced ejection fraction: Insights from the echocardiographic substudy of the VICTORIA trial - Tromp, Jasper; Lam, Carolyn S P; Alemayehu, Wendimagegn; de Filippi, Christopher R; Melenovský, Vojtěch; Sliwa, Karen; Lopatin, Yuri; Arango, Juan Luis; Bahit, M Cecilia; Roessig, Lothar; O'Connor, Christopher M; Shah, Palak; et al. (European journal of heart failure, 2024)
AIMS: Reverse ventricular remodelling, defined as a decrease in left ventricular end-systolic volume indexed to body surface area (LVESVI) or an increase in left ventricular ejection fraction (LVEF), is associated with improved clinical outcomes in patients with heart failure with reduced ejection fraction (HFrEF). However, the underlying pathophysiological mechanisms remain unclear. METHODS AND RESULTS: We evaluated paired core-lab assessed echocardiograms and measurements of 92 biomarkers at baseline and 8 months thereafter in 419 participants with HFrEF. Reverse ventricular remodelling was defined as a >5% LVEF increase or >15% LVESVI relative decrease between baseline and 8 months. We evaluated the association between baseline biomarkers and their changes with reverse ventricular remodelling in the prospectively randomized controlled VICTORIA (Vericiguat Global Study in Subjects With Heart Failure With Reduced Ejection Fraction) trial. Of 419 patients (median age 66 [interquartile range 57-74] years, 27.4% women), 206 (49.2%) had reverse ventricular remodelling (either a 5% LVEF increase or a 15% LVESVI decrease). There were no differences in baseline biomarker concentrations between patients with versus those without reverse ventricular remodelling on follow-up. However, in patients with reverse ventricular remodelling there were significant decreases in biomarkers relating to inflammation and cardiac metabolism; particularly the tumour necrosis factor superfamily member 13B (ratio 0.82, 95% confidence interval [CI] 0.77-0.88), growth differentiation factor-15 (ratio 0.74, 95% CI 0.66-0.84), and insulin-like growth factor binding protein 7 (ratio 0.80, 95% CI 0.73-0.88). CONCLUSIONS: Reverse ventricular remodelling in patients with HFrEF is associated with a decrease of biomarkers related to inflammation and cardiac metabolism.
Keywords: echokardiografie; Stroke Volume; Female; biologické markery; Biomarkers; ženské pohlaví; Heart Failure; funkce levé komory srdeční; lidé; srdeční selhání; Echocardiography; Ventricular Remodeling; prospektivní studie; Male; Aged; Prospective Studies; tepový objem; remodelace komor; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Ventricular Function, Left; Humans